Bronchial blocker placement for massive hemoptysis - Ryan L. Loncar; Elliott J. Chiartas; Sheryl Modlin; Jibran Ikram; Sabry Ayad (Saudi Journal of Anaesthesia)
Massive hemoptysis is a life-threatening pathology requiring emergent intervention to prevent airway obstruction and hypovolemic shock. Intubation followed by lung isolation should be urgently performed. We elected to place Fuji Uniblocker (Fuji Systems Corporation, Tokyo, Japan) through an endotracheal tube to isolate a hemorrhage secondary to a cavitary lung lesion caused by a large pulmonary embolus. This article examines lung isolation strategies and addresses the advantages and disadvantages in patients with massive hemoptysis.